'Wittig and Davis, Woolf and Solanas (…) simmer within me': Reading Feminist Archives in the Queer Writing of Paul B. Preciado. Issue 3 (November 2018) - Evans, Elliot
Abstract : This article considers the relation between contemporary queer and transgender theory and the 'second wave' of feminism. Specifically, it explores the ways in which transgender theorist Paul B. Preciado's Testo Junkie: Sex, Drugs, and Biopolitics (2008) calls on feminist theorists, artists and activists of the second wave to explore transgender experience and embodiment, and to rethink gender in light of the new era of biocapitalism Preciado proposes. The article questions the way in which trajectories of feminism are conceived of (most famously through the 'waves' metaphor), and finally calls for a 'scavenger methodology' as a way to consider the formation of feminist and queer archives.